Studi dan Aplikasi Elektroda FeTiO3-TiO2/Ti untuk Degradasi Reactive Blue 160 dengan Metode Fotoelektrokatalisis: Study and Application of Photoelectrocatalytic FeTiO3-TiO2/ Ti Electrode to High-Degradation of Reactive Blue 160 - Thamrin Azis; Maulidiyah Maulidiyah; Muhammad Nurdin; Muh. Zakir Muzakkar; Ratna; La Ode Abd Kadir; Viesta Valentin Octavian; T Nurwahida; C Bijang; Haris W (KOVALEN: Jurnal Riset Kimia, 2021)
The manufacture of titanium dioxide (TiO2) electrodes is made by anodizing method and coated with ilmenite (FeTiO3) through a dip-coating technique. The ilmenite (FeTiO3) coated TiO2/Ti plate electrode was developed for the degradation of the reactive blue 160 dye under photoelectrocatalytic UV and Visible light irradiation. The performance of FeTiO3-TiO2 / Ti composites degrades reactive blue 160 under UV irradiation and is visible photoelectrocatalytically compared to TiO2. The results of XRD characterization of TiO2 crystals in the form of anatase at 2θ, namely 35.1 ° (110), and the substitution of Fe dopant on TiO2 in the form of anatase and rutile crystals. FTIR data indicated the presence of Fe-O bonds at wave numbers <700 nm. SEM-EDX results showed a thin layer of FeTiO3 was formed, indicating that the dip-coating method was effective in the coating process. The performance of the FeTiO3-TiO2 / Ti electrode has the highest activity against the oxidation process under visible light than the TiO2/Ti electrode. The results of degradation of reactive blue 160 dye with a concentration of 0.5 ppm by photoelectrocatalytic showed that the TiO2 / Ti and FeTiO3-TiO2/Ti electrodes were active in visible irradiation with degradation rate constants of 48% and 69%. Keywords: Electrodes, ilmenite, TiO2 / Ti, degradation, reactive blue 160, photoelectrocatalysis